Ya manga sulat ni Pablo adti manga mangintu-uway dun ni syudad na Tessalonika 1st and 2nd Thessalonians with study guide. - Overseas Missionary Fellowship (Davao City Overseas Missionary Fellowship, 2008)
"Paul's letters to the believers in the city of Thessalonica"--Provided by publisher.
In Tagakaulo.
Keywords: Bible. -- 2008 -- Criticism, interpretation, etc; Bible. -- Study guide; Bible. -- Versions; Tagakaolo language -- Texts